2007
DOI: 10.1016/j.jrp.2007.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Culture, method, and the content of self-concepts: Testing trait, individual–self-primacy, and cultural psychology perspectives

Abstract: Three theoretical perspectives on cultural universals and differences in the content of self-concepts were tested in individualistic (United States, n = 178; Australia, n = 112) and collectivistic (Mexico, n = 157; Philippines, n = 138) cultures, using three methods of self-concept assessment. Support was found for both trait perspectives and the individual-self-primacy hypothesis. In contrast, support for cultural psychology hypotheses was limited because traits and other personal attributes were not more sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 61 publications
(105 reference statements)
5
61
0
Order By: Relevance
“…This becomes evident when one considers the preferred categories of personality description beyond traits, the contextualization of descriptions, the role of social distance from the described person, and the substantiation of differences across personality domains. We found that Blacks made more descriptions using behaviors, preferences, and relational contextualization than the other groups (however, all three groups made few references to social roles and identities); they used the fewest traits for self-descriptions but had overall small differences across social distance; they used relatively few traits and little contextualizing information for agentic descriptions and and communal descriptions (Del Prado et al, 2007;Sedikides et al, 2005) and the psycholexical hypothesis (Saucier & Goldberg, 2001). This integration of different perspectives is in line with efforts to bring the study of trait use beyond the juxtaposition of the trait and cultural psychology perspectives (Church, 2000(Church, , 2009.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…This becomes evident when one considers the preferred categories of personality description beyond traits, the contextualization of descriptions, the role of social distance from the described person, and the substantiation of differences across personality domains. We found that Blacks made more descriptions using behaviors, preferences, and relational contextualization than the other groups (however, all three groups made few references to social roles and identities); they used the fewest traits for self-descriptions but had overall small differences across social distance; they used relatively few traits and little contextualizing information for agentic descriptions and and communal descriptions (Del Prado et al, 2007;Sedikides et al, 2005) and the psycholexical hypothesis (Saucier & Goldberg, 2001). This integration of different perspectives is in line with efforts to bring the study of trait use beyond the juxtaposition of the trait and cultural psychology perspectives (Church, 2000(Church, , 2009.…”
Section: Discussionmentioning
confidence: 75%
“…We started with an examination of agency-communion, which are broad constructs that have been suggested to capture substantial cross-cultural differences in personality descriptions (Del Prado et al, 2007;Sedikides et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In self-description tasks, participants write a higher proportion of individual-self aspects than collectiveself aspects. That pattern replicates across (a) participants both with an independent and interdependent self-construal (Gaertner et al 1999, Investigation 4), (b) Chinese and American or Canadian participants (Ross et al 2002;Trafimow et al 1991), Philippino, Mexican, Australian, and American participants (del Prado et al 2007), and (c) experimenter-activated priming of individual and collective self (Trafimow et al 1991;Ybarra and Trafimow 1998, Experiment 3). Moreover, at the implicit level, participants from the US, China, and Japan evaluate the individual self more positively than the relational friend (i.e., best friend) or the collective self (i.e., ingroup member) (Yamaguchi et al 2007).…”
Section: Comparative Testingmentioning
confidence: 66%